Positive electrode material and sodium ion battery

Through multi-element co-doping of the sodium layer and the transition metal layer, the O-Na(A)-O interaction is enhanced, and the problem of phase transformation of layered positive electrode materials under high pressure is solved, and structural stability and cyclic performance are improved.

CN119447280APending Publication Date: 2025-02-14HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310961005.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Laminated cathode material will undergo irreversible phase change during high-pressure cycles, making it difficult to guarantee the long cycle life of the material, which is not conducive to actual commercial use.

Method used

Through multi-element co-doping of the sodium layer and the transition metal layer, the O-Na(A)-O interaction between adjacent transition metal layers is synergistically enhanced, adverse phase change of the positive electrode material under high pressure is suppressed, and structural stability is improved.

Benefits of technology

While maintaining the electrochemically active pair, the structure stability of the sodium-electrode phase is regulated through multi-ion collaborative doping, layer slip and layer collapse under high voltage, and the high-voltage stability and cyclic performance of the positive electrode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447280A_ABST
    Figure CN119447280A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a positive electrode material, the molecular formula of which is Na1-naAn + a [TmbM1cM2d] O2, A is one or more alkali metal or alkaline earth metal elements in which the feed property psi A meets the condition that psi A is greater than or equal to 0.9 psi Na and less than psi Na; tm is a combination of one or more elements of Fe, Mn and Co and Ni, and M1 is a feed property psi M1gt; m < 2 > is one or more metal elements in Psi 0.6 Tmmax, and M < 2 > is feed Psi 0.6 M < 2 > gt; psi 0.6 Tmmax is one or more metal elements selected from the group consisting of Psi 0.6 Tmmax; 0 < a < = 0.1, 0.3 < = b < 1, 0 < c < = 0.6, 0 < = d < = 0.2, b + c + d = 1, and values of a, b, c and d enable the positive electrode material to maintain charge balance. According to the positive electrode material, through multi-element co-doping of the sodium layers and the transition metal layers, the interaction between the adjacent transition metal layers is synergistically enhanced, and the structural stability of the positive electrode material at a high sodium removal amount can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of sodium ion batteries, and in particular to a positive electrode material and a sodium ion battery. Background Art

[0002] Due to the shortage of lithium resources and their uneven distribution around the world, the cost of using lithium-ion batteries is too high, which seriously restricts the large-scale use of lithium-ion batteries. Sodium resources are widely distributed, low-cost, and have similar physical and chemical properties to lithium. Therefore, sodium-ion batteries are considered to be the most promising and viable alternative to lithium-ion batteries. Layered transition metal oxides are based on reversible intercalation reactions, have simple synthesis methods and relatively high capacity, and are considered to be the most promising sodium-based cathode route for industrialization. However, layered cathode materials undergo irreversible phase changes during high-voltage cycling, which makes it difficult to ensure the long cycle life of such materials, which is not conducive to actual commercial applications. Therefore, it is urgent to find a type of sodium-ion battery cathode material with high reversible specific capacity and stable structure. Summary of the invention

[0003] In view of this, an embodiment of the present application provides a positive electrode material for a sodium ion battery, wherein the doping elements of the sodium layer and the transition metal layer are rationally designed based on the power feeding property, and the O-Na(A)-O interaction between adjacent transition metal layers is synergistically enhanced through multi-element co-doping of the sodium layer and the transition metal layer, thereby suppressing the adverse phase change of the positive electrode material under high pressure, i.e., when highly de-sodiumized, and improving the structural stability of the positive electrode material at a high de-sodiumization amount.

[0004] The first aspect of the present application provides a positive electrode material, wherein the molecular formula of the positive electrode material is Na 1-na A n+ a [Tm b M 1 c M 2 d ]O2, wherein A is one or more alkali metal or alkaline earth metal elements with a power feeding property ψA satisfying 0.9ψNa≤ψA<ψNa; Tm is a combination of one or more elements of Fe, Mn, Co and Ni, M 1 is the feeding characteristic ψM 1 Satisfy ψM 1 >ψ 0.6 Tm max One or more metal elements, and M 1 M is an inert element that does not provide charge compensation. 2 The feeding characteristic ψ 0.6 M 2 Satisfy ψ 0.6 M 2 >ψ 0.6Tm max One or more metal elements, and M 2 An active element that provides charge compensation; 0<a≤0.1, 0.3≤b<1, 0<c≤0.6, 0≤d≤0.2, b+c+d=1, and the values ​​of a, b, c, d enable the positive electrode material to maintain charge balance;

[0005] Among them, ψA=χO-χA, ψM 1 =χO-χM 1 , χO is the effective electronegativity of O, χA is the effective electronegativity of A, χM 1 M 1 The effective electronegativity of 0.6 Tm max is the maximum chargeability of Tm when the amount of sodium removal of the positive electrode material is greater than or equal to 0.6, where ψ 0.6 Tm = ψiniTm-0.6*(ψiniTm-ψendTm), ψiniTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 0, and ψendTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 1; ψ 0.6 M 2 =ψiniM 2 -0.6*(ψiniM 2 -ψendM 2 ), ψiniM 2 When the amount of sodium removed from the positive electrode material is 0, M 2 The feeding property, ψendM 2 When the amount of sodium removed from the positive electrode material is 1, M 2 The feeding property.

[0006] In the embodiment of the present application, the A replaces the Na site to achieve sodium layer doping, and the M 1 、M 2 Replace the Tm site to achieve transition metal layer doping. 1 As an electrochemically inert element, it cannot provide charge compensation, and its charge feeding property remains unchanged during the entire de-sodium process. 2 As an active electrode pair, the feeding property decreases with the increase of sodium removal. 2 The feeding characteristic is limited to the feeding characteristic ψ of 0.6 0.6 M 2 Make a comparison.

[0007] The positive electrode material of the embodiment of the present application is a layered positive electrode material, which can be used as a positive electrode material for a sodium ion battery. The positive electrode material is rationally designed for the doping elements of the sodium layer and the transition metal layer based on the feeding property. Through the multi-element co-doping of the sodium layer and the transition metal layer, the interlayer force of the adjacent transition metal TM layer, that is, the O-Na-O force, is synergistically enhanced, thereby suppressing the unfavorable phase change of the positive electrode material under high pressure, that is, when highly de-sodiumized, and improving the structural stability of the positive electrode material when the amount of de-sodiumization is high. Specifically, starting from the electrostatic attraction, the O-Na(A) force is regulated by both the sodium layer and the transition metal layer. On the one hand, the transition metal layer doped with the element M 1 、M 2 The feeding property of ψM is as large as possible 1 >ψ 0.6 Tm max , ψ 0.6 M 2 >ψ 0.6 Tm max In the structural unit MO-Na(A), an electron-donating effect is presented to O, and the electron cloud density of O is increased to enhance the interaction between O and Na. On the other hand, the electron-donating property of the doped element A in the sodium layer is as small as possible, 0.9ψNa≤ψA<ψNa, and an electron-pulling effect is presented to O, thereby enhancing the O-Na related interaction. Under the synergistic effect of "one-donating and one-pulling" doping of the sodium layer and the transition metal layer, the interaction between O and Na is significantly improved, thereby having a more obvious synergistic inhibitory effect on the slip of the transition metal layer under high pressure. The positive electrode material of the embodiment of the present application can regulate the structural stability of the sodium positive electrode phase through multi-ion synergistic doping without reducing the electrochemically active electrode as much as possible, and inhibit the layer slip and layer collapse under high pressure.

[0008] In this application, the effective electronegativity of A is χA, M 1 The effective electronegativity χM 1 It can be calculated using the following formula or obtained through query:

[0009] Among them, n * For element M n+ The effective principal quantum number of

[0010] Among them, I m For element M n+ The n-level ionization energy;

[0011] Where R is the Rydberg constant, R = 13.6 eV;

[0012] Among them, r M For element M n+ The coordination radius.

[0013] In this application, ψ0.6 Tm max It depends on the type of Tm selected in the positive electrode material. For example, when Tm includes Ni, Fe, Mn and Co at the same time, ψ 0.6 Tm max =(ψ 0.6 Fe,ψ 0.6 Mn,ψ 0.6 Co,ψ 0.6 Ni) max , due to calculation, we know that ψ 0.6 Fe=1.698,ψ 0.6 Mn=1.657,ψ 0.6 Co=1.590,ψ 0.6 Ni=1.540, so ψ 0.6 Tm max =1.698. Similarly, when Tm includes Ni, Mn and Co, ψ 0.6 Tm max =(ψ 0.6 Mn,ψ 0.6 Co,ψ 0.6 Ni) max , ψ 0.6 Tm max =1.657. Similarly, when Tm includes Ni, Mn and Fe, ψ 0.6 Tm max =(ψ 0.6 Fe,ψ 0.6 Mn,ψ 0.6 Ni) max , ψ 0.6 Tm max =1.698. Similarly, when Tm includes both Ni and Mn, ψ 0.6 Tm max =(ψ 0.6 Mn,ψ 0.6 Ni) max , ψ 0.6 M max =1.657. Among them, ψ0.6Tm=ψiniTm-0.6*(ψini-ψend), where ψiniTm refers to the power feeding property when the amount of sodium removal of the positive electrode material is 0, and ψendTm refers to the power feeding property when the amount of sodium removal of the positive electrode material is 1.

[0014] In the implementation mode of the present application, the sodium element and the oxygen element form a sodium layer, and the doping element A is one or more alkali metals or alkaline earth metal elements whose feeding property ψA satisfies 0.9ψNa≤ψA<ψNa. The doping element A replaces the Na site of the sodium layer in the positive electrode material and forms a partial OA structure in the sodium layer. The value of a represents the doping amount of the doping element A. In the present application, 0<a≤0.1. In some implementation modes of the present application, 0.01≤a≤0.06. The incorporation of a suitable amount of doping element A in the sodium layer can, on the one hand, better present an electron-pulling effect on O in the positive electrode material, thereby enhancing the O-Na(A) effect, which is beneficial to improving the structural stability of the positive electrode material under high voltage; on the other hand, it can avoid the occurrence of impurities or element segregation in the synthesis of the positive electrode material; and from the perspective of capacity, the appropriate doping of the doping element A has less effect on the amount of sodium removal, which can meet the requirement of more than 0.6 of the maximum sodium removal amount of the positive electrode; from the perspective of cost, Na is cheaper than other doping elements, and appropriate doping has a higher performance-efficiency ratio.

[0015] In the implementation manner of the present application, the element Tm is a transition metal layer element, specifically one or more elements of Ni, Fe, Mn, and Co, and the element Tm and the oxygen element form a transition metal layer. In some embodiments of the present application, 0.4≤b≤0.9. Controlling the content of the Tm element within a suitable range is conducive to the positive electrode material obtaining a stable layered structure and maintaining the high capacity and other characteristics of the positive electrode material.

[0016] In the implementation mode of the present application, M 1 It is an inert element that does not provide charge compensation, that is, it is a non-electrochemically active element. The doping element M 1 Replace the Tm site in the transition metal layer and form part of the M 1 -O structure. The value of c represents M 1 In this application, M 1 It is an inert element, and its doping amount should not be too much, 0<c≤0.6. In some embodiments of the present application, 0.05≤c≤0.2. The transition metal Tm layer is doped with the element M 1 Controlling the amount of within a suitable range is beneficial to improving the electron cloud density of O through its electron donation effect on O, thereby enhancing the O-Na interaction, inhibiting high-voltage phase transition, and improving the structural stability of the positive electrode material under high voltage; and as a material guest doping element, controlling it within a suitable range is beneficial to the synthesis of pure phase materials, avoiding surface segregation caused by insufficient solid solubility, and at the same time can better ensure the capacity of the positive electrode material.

[0017] In the implementation mode of the present application, M 2 To provide active elements for charge compensation, i.e. electrochemically active elements, doping elements M 2Replace the Tm site in the transition metal layer and form part of the M 2 -O structure. Different from the lithium battery positive electrode, the sodium battery positive electrode has more active electrode candidates. 2 , which is beneficial for example, V, Cr, Cu, Ru, Ir, etc., which have strong electron donating ability to coordinate O under high sodium removal, and can be appropriately introduced to further enhance the interaction force between adjacent Tm layers under high pressure. The value of d represents M 2 In some embodiments of the present application, 0≤d≤0.1. The transition metal Tm layer is doped with the element M 2 The amount of Na is controlled within a suitable range. On the one hand, it is beneficial to increase the electron cloud density of O through its electron donation effect on O, so as to enhance the O-Na interaction and improve the structural stability of the positive electrode material under high voltage. On the other hand, appropriate doping is beneficial to the synthesis of pure phase, and for cost considerations, appropriate doping has a higher performance-efficiency ratio.

[0018] ψNa=2.416, that is, A can be an element with 2.174≤ψA<2.416. In some embodiments of the present application, A is selected from one or more elements of Li, Mg, Ca, Sr, and Ba. Li, Mg, Ca, Sr, and Ba have a smaller feeding property than Na. In this way, element A can present a stronger electron-pulling effect on O than Na, thereby enhancing the O-Na correlation effect. It can be understood that the feeding property of element A is as small as possible, which is more conducive to the enhancement of the O-Na correlation effect.

[0019] In the present application, ψM 1 >ψ 0.6 Tm max , when Tm includes Ni, Fe, Mn and Co at the same time, ψ 0.6 Tm max =1.698. When Tm includes Ni, Mn and Co at the same time, ψ 0.6 Tm max =1.657. In some embodiments of the present application, the M 1 It can be one or more elements selected from Li, Ti, Zn, Mg, Sn, Al, Y, La, Nd, and Zr. 1 With a value greater than ψ 0.6 Tm max The feeding property can make M 1 When the amount of sodium removal of the positive electrode material is x, 0.6≤x≤1, the electron donation to O is greater than that of the original transition metal element Tm, and the coordinated O has a higher electron density, which enhances the O-Na-O interaction. It can be understood that the element M 1 The feeding property is as large as possible while satisfying the principle of equivalent substitution, which is more conducive to the enhancement of O-Na related effects.

[0020] In the implementation mode of the present application, ψ 0.6 M 2 >ψ 0.6 Tm max , the M 2 It can be one or more elements selected from V, Cr, Ru, Cu, and Ir. 0.6 M 2 >ψ 0.6 Tm max Can make M 2 When the amount of sodium removal of the positive electrode material is x, 0.6≤x≤1, the electron donation to O is greater than that of the original transition metal element Tm, and the coordinated O has a higher electron density, which enhances the O-Na-O interaction. It can be understood that the element M 2 The feeding property ψ 0.6 M 2 As large as possible while satisfying the principle of equivalent substitution is more conducive to the enhancement of O-Na related effects.

[0021] In the embodiment of the present application, the positive electrode material is a spherical, polygonal or lamellar particle, and the particle size D50 is 2 μm-20 μm. The suitable particle size is conducive to the preparation of the positive electrode sheet.

[0022] In the embodiment of the present application, the compaction density of the positive electrode material is 2.8 g·cm -3 -3.2g cm -3 The positive electrode material has a higher compaction density, which is beneficial to the improvement of battery capacity.

[0023] In the embodiment of the present application, the 0.2c charging gram capacity of the positive electrode material is 140 mAh g -1 -180mAh g -1 The positive electrode material has a higher gram capacity, which is beneficial to the improvement of battery capacity.

[0024] In the embodiment of the present application, the crystal structure of the positive electrode material is an α-NaFeO2 hexagonal layered structure. The α-NaFeO2 hexagonal layered structure can make the positive electrode material have good electrochemical performance.

[0025] A second aspect of the present application provides a method for preparing a positive electrode material, comprising:

[0026] According to the molecular formula of the positive electrode material Na 1-na A n+ a [M b M 1 c M 2 d ]O2, sodium source, A source, Tm source, M 1 Source, M2 The sources are mixed to obtain a mixed material;

[0027] The mixed material is calcined in an oxygen atmosphere to obtain a positive electrode material.

[0028] In the embodiment of the present application, the sodium source includes a sodium-containing compound, and the sodium-containing compound includes one or more of sodium carbonate, sodium nitrate, sodium oxide, sodium peroxide and sodium hydroxide; the A source includes an A-containing compound, and the A-containing compound includes one or more of carbonates, nitrates, oxides, peroxides and hydroxides containing A; the Tm source includes a Tm-containing compound, and the Tm-containing compound includes one or more of metal oxides, metal carbonates, metal nitrates and metal hydroxides containing Tm; the M 1 Sources include M 1 Compound, the compound containing M 1 Compounds including M 1 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides; the M 2 Sources include M 2 Compound, the compound containing M 2 Compounds including M 2 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides.

[0029] The method for preparing the positive electrode material in the embodiment of the present application has a simple process and does not require complicated steps during the doping process.

[0030] The third aspect of the embodiment of the present application provides a positive electrode sheet, which includes the positive electrode material described in the first aspect of the embodiment of the present application. The positive electrode sheet prepared by using the positive electrode material of the embodiment of the present application has a high capacity and high structural stability, and can effectively improve the cycle performance of the sodium ion battery while maintaining the high capacity of the sodium ion battery.

[0031] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on the positive electrode current collector, and the positive electrode active layer includes the positive electrode material.

[0032] A fourth aspect of the present application provides a sodium ion battery, the sodium ion battery comprising a positive electrode sheet, a negative electrode sheet, and an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises the positive electrode sheet described in the third aspect of the present application. The sodium ion battery of the present application adopts the positive electrode material Na 1-na A n+ a [Tm b M 1 c M 2 d]O2 can effectively improve the cycle performance of sodium-ion batteries while maintaining their high capacity.

[0033] The present application also provides an electrical device, wherein the electrical device comprises the sodium ion battery described in the fourth aspect of the present application. The electrical device using the sodium ion battery of the present application has high stability.

[0034] In the implementation manner of the present application, the electrical equipment includes electronic equipment, energy storage system, communication equipment or communication base station. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the structure of the positive electrode sheet 10 provided in an embodiment of the present application;

[0036] Figure 2 A schematic diagram of the structure of a sodium ion battery 100 provided in an embodiment of the present application;

[0037] Figure 3 A schematic diagram of the structure of an electric device 200 provided in an embodiment of the present application;

[0038] Figure 4 The positive electrode material Na provided in Example 5 of the present application 0.94 Mg 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.067 Ti 0.133 EDS element distribution diagram of O2;

[0039] Figure 5 A curve diagram of the maximum sodium removal amount before phase change of the positive electrode material provided in Example 9 of the present application;

[0040] Figure 6 A phase change capacity curve diagram of the positive electrode material provided in Example 9 of the present application;

[0041] Figure 7 A curve diagram of the maximum sodium removal amount before phase change of the positive electrode material provided in Comparative Example 7 of the present application;

[0042] Figure 8 This is a phase change capacity curve diagram of the positive electrode material provided in Comparative Example 7 of the present application. DETAILED DESCRIPTION

[0043] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0044] Sodium layered transition metal oxides are based on reversible intercalation reactions, have simple synthesis methods and relatively high capacity, and are considered the most promising sodium battery cathode route for industrialization. However, due to the structure, the Na layer spacing of the P3 phase of the sodium layered transition metal oxide cathode under high pressure is wider than the Li layer spacing of the lithium battery cathode, resulting in a weaker interaction between the adjacent transition metal Tm layers, that is, a weaker O-Na-O interaction. When the amount of sodium removal reaches 0.6 or more, the O-Na-O interaction is insufficient, and an irreversible phase transition caused by Tm layer slippage, that is, a PO phase transition, is prone to occur, which makes it difficult to ensure the long cycle life of the sodium layered transition metal oxide, which is not conducive to actual commercial application. In order to solve this technical problem, the present application is designed from the bottom principle without reducing the electrochemically active electrode couple, and the feeding principle is used to screen the doping ions of the sodium layer and the transition metal layer in a targeted manner. The sodium layer and the transition metal layer are synergistically doped. The strategy is adopted to modify the existing sodium layered transition metal oxides, maximize the O-Na-O interaction force, enhance the stability of adjacent transition metal layers, inhibit phase change under high pressure and increase the amount of sodium removal before the phase change, thereby improving the high-voltage stability of the positive electrode material and enabling the positive electrode material to have a more stable high-capacity performance.

[0045] The present invention provides a positive electrode material, the molecular formula of which is Na 1-na A n+ a [Tm b M 1 c M 2 d ]O2, the positive electrode material is a doped sodium transition metal oxide, wherein A is one or more alkali metal or alkaline earth metal elements with a power feeding property ψA satisfying 0.9ψNa≤ψA<ψNa, and A replaces the Na site; Tm is a combination of one or more elements of Fe, Mn, Co and Ni, M 1 is the feeding characteristic ψM 1 Satisfy ψM 1 >ψ 0.6 Tm max One or more metal elements, and M 1 M is an inert element that does not provide charge compensation. 2 The feeding characteristic ψ 0.6 M 2 Satisfy ψ 0.6 M 2 >ψ 0.6 Tm max One or more metal elements, and M 2 To provide active elements for charge compensation, M 1 、M 2Replace the Tm site; 0<a≤0.1, 0.3≤b<1, 0<c≤0.6, 0≤d≤0.2, b+c+d=1, and the values ​​of a, b, c, d make the positive electrode material maintain charge balance;

[0046] Among them, ψA=χO-χA, ψM 1 =χO-χM 1 , χO is the effective electronegativity of O, χA is the effective electronegativity of A, χM 1 M 1 The effective electronegativity of 0.6 Tm max is the maximum chargeability of Tm when the amount of sodium removed from the positive electrode material is greater than or equal to 0.6, where ψ 0.6 Tm = ψiniTm-0.6*(ψiniTm-ψendTm), ψiniTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 0, and ψendTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 1; ψ 0.6 M 2 =ψiniM 2 -0.6*(ψiniM 2 -ψendM 2 ), ψiniM 2 When the amount of sodium removed from the positive electrode material is 0, M 2 The feeding property, ψendM 2 When the amount of sodium removed from the positive electrode material is 1, M 2 The feeding property.

[0047] In this application, M 1 As an electrochemically inert element, it cannot provide charge compensation, and its charge feeding property remains unchanged during the entire de-sodium process. 2 As an active electrode pair, the feeding property decreases with the increase of sodium removal. 2 The feeding characteristic is limited to the feeding characteristic ψ of 0.6 0.6 M 2 χO and χA are fixed values, which can be obtained by looking up the table.

[0048] The positive electrode material of the embodiment of the present application is a layered positive electrode material, which can be used as a positive electrode material for a sodium ion battery. The positive electrode material is rationally designed for the doping elements of the sodium layer and the transition metal layer based on the feeding property. Through the multi-element co-doping of the sodium layer and the transition metal layer, the interlayer force of the adjacent transition metal TM layer, that is, the O-Na-O force, is synergistically enhanced, thereby suppressing the unfavorable phase change of the positive electrode material under high pressure, that is, when highly de-sodiumized, and improving the structural stability of the positive electrode material when the amount of de-sodiumization is high. Specifically, starting from the electrostatic attraction, the O-Na(A) force is regulated by both the sodium layer and the transition metal layer. On the one hand, the transition metal layer doped with the element M 1 、M 2The feeding property of ψM is as large as possible 1 >ψ 0.6 Tm max , ψ 0.6 M 2 >ψ 0.6 Tm max In the structural unit MO-Na(A), an electron-donating effect is presented to O, and the electron cloud density of O is increased to enhance the interaction between O and Na. On the other hand, the electron-donating property of the doped element A in the sodium layer is as small as possible, 0.9ψNa≤ψA<ψNa, and an electron-pulling effect is presented to O, thereby enhancing the O-Na related interaction. Under the synergistic effect of "one-donating and one-pulling" doping of the sodium layer and the transition metal layer, the interaction between O and Na is significantly improved, thereby having a more obvious synergistic inhibitory effect on the slip of the transition metal layer under high pressure. The positive electrode material of the embodiment of the present application can regulate the structural stability of the sodium positive electrode phase through multi-ion synergistic doping without reducing the electrochemically active electrode as much as possible, and inhibit the layer slip and layer collapse under high pressure.

[0049] In this application, the effective electronegativity of A is χA, M 1 The effective electronegativity χM 1 It can be calculated using the following formula:

[0050] Among them, n * For element M n+ The effective principal quantum number of

[0051] Among them, I m For element M n+ The n-level ionization energy;

[0052] Where R is the Rydberg constant, R = 13.6 eV;

[0053] Among them, r M For element M n+ The coordination radius.

[0054] In this application, ψ 0.6 Tm max It depends on the type of Tm selected in the positive electrode material. For example, when Tm includes Ni, Fe, Mn and Co at the same time, ψ 0.6 Tm max =(ψ 0.6 Fe,ψ 0.6 Mn,ψ 0.6 Co,ψ 0.6 Ni) max , due to calculation, we know that ψ 0.6 Fe=1.698,ψ 0.6 Mn=1.657,ψ 0.6Co=1.590,ψ 0.6 Ni=1.540, so ψ 0.6 Tm max =1.698. Similarly, when Tm includes Ni, Mn and Co, ψ 0.6 Tm max =(ψ 0.6 Mn,ψ 0.6 Co,ψ 0.6 Ni) max , ψ 0.6 Tm max =1.657. Similarly, when Tm includes Ni, Mn and Fe, ψ 0.6 Tm max =(ψ 0.6 Fe,ψ 0.6 Mn,ψ 0.6 Ni) max , ψ 0.6 Tm max =1.698. Similarly, when Tm includes both Ni and Mn, ψ 0.6 Tm max =(ψ 0.6 Mn,ψ 0.6 Ni) max , ψ 0.6 M max =1.657. Among them, ψ0.6Tm=ψiniTm-0.6*(ψini-ψend), where ψiniTm refers to the power feeding property when the amount of sodium removal of the positive electrode material is 0, and ψendTm refers to the power feeding property when the amount of sodium removal of the positive electrode material is 1.

[0055] In the implementation mode of the present application, the sodium element and the oxygen element form a sodium layer, and the doping element A is one or more alkali metals or alkaline earth metal elements whose feeding property ψA satisfies 0.9ψNa≤ψA<ψNa. The doping element A replaces the Na site of the sodium layer in the positive electrode material to form a partial OA structure in the sodium layer. ψNa=2.416, 0.9ψNa=2.174, that is, A can be an element of 2.174≤ψA<2.416. In the layered positive electrode material, the sodium layer and the transition metal Tm layer are arranged alternately. Selecting an alkali metal or alkaline earth metal with suitable feeding property to dope the sodium layer is beneficial to avoid the problem of metal elements that do not match the coordination octahedron of the sodium layer being doped into the sodium layer, resulting in greater damage to the coordination environment of the sodium layer, thereby better maintaining the original crystal structure of the sodium layer.

[0056] In some embodiments of the present application, A is selected from one or more elements of Li, Mg, Ca, Sr, and Ba. ψLi = 2.413, ψMg = 2.206, ψCa = 2.280, ψSr = 2.301, ψBa = 2.316. Li, Mg, Ca, Sr, and Ba have a smaller feeding property than Na, so that element A can present a stronger electron-pulling effect on O than Na, thereby enhancing the O-Na correlation effect. It can be understood that the feeding property of element A is as small as possible, which is more conducive to the enhancement of the O-Na correlation effect.

[0057] In the implementation mode of the present application, the value of a represents the doping amount of the doping element A. In the implementation mode of the present application, 0<a≤0.1. In some embodiments of the present application, the value of a can be, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1. In some implementation modes of the present application, 0.01≤a≤0.06. The incorporation of a suitable amount of doping element A in the sodium layer can, on the one hand, better present an electron-pulling effect on O in the positive electrode material, thereby achieving the enhancement of the O-Na(A) effect, which is beneficial to improving the structural stability of the positive electrode material under high voltage; on the other hand, it can avoid the occurrence of impurities or element segregation in the synthesis of the positive electrode material; and from the perspective of capacity, the appropriate doping of the doping element A has less effect on the amount of sodium removal, which can better meet the requirement of a maximum sodium removal amount of more than 0.6 for the positive electrode; from the perspective of cost, Na is cheaper than other doping elements, and appropriate doping has a higher performance-to-performance ratio.

[0058] In the implementation mode of the present application, the element Tm is a transition metal layer element, specifically one or more elements of Ni, Fe, Mn, and Co, and the element Tm forms a transition metal layer with the oxygen element. In the implementation mode of the present application, 0.3≤b<1. In some embodiments of the present application, the value of b can be, for example, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9. In some embodiments of the present application, 0.4≤b≤0.9. Controlling the content of the Tm element within a suitable range is conducive to the positive electrode material obtaining a stable layered structure and maintaining the high capacity and other characteristics of the positive electrode material. As a common 3d transition metal active electrode pair, Tm is controlled within a suitable range to provide sufficient charge compensation to meet the demand for sodium removal, that is, to maintain capacity; and Tm, as the main element of the material, is within a suitable content range to facilitate the material to obtain a stable layered structure.

[0059] In this application, M 1 , M 2 The introduction of can increase the electron density of coordinated oxygen in the positive electrode material under high sodium removal, thereby strengthening the Na interlayer force.

[0060] In the implementation mode of the present application, M 1It is an inert element that does not provide charge compensation, that is, it is a non-electrochemically active element. The doping element M 1 Replace the Tm site in the transition metal layer and form part of the M 1 -O structure. The value of c represents M 1 In some embodiments of the present application, 0<c≤0.6. In some embodiments of the present application, the value of c can be, for example, 0.05, 0.1, 0.15, 0.2, 0.23, 0.25, 0.3, 0.4, 0.5, 0.6. In some embodiments of the present application, 0.05≤c≤0.2. The transition metal Tm layer is doped with the element M 1 Controlling the amount of within a suitable range is beneficial to improving the electron cloud density of O through its electron donation effect on O, thereby enhancing the O-Na interaction, inhibiting high-voltage phase transition, and improving the structural stability of the positive electrode material under high voltage; and as a material guest doping element, controlling it within a suitable range is beneficial to the synthesis of pure phase materials, avoiding surface segregation caused by insufficient solid solubility, and at the same time can better ensure the capacity of the positive electrode material.

[0061] In the present application, ψM 1 >ψ 0.6 Tm max , when Tm includes Ni, Fe, Mn and Co at the same time, ψ 0.6 Tm max =1.698. When Tm includes Ni, Mn and Co at the same time, ψ 0.6 Tm max =1.657. When Tm includes Ni, Mn and Fe at the same time, ψ 0.6 Tm max =1.698. When Tm includes both Ni and Mn, ψ 0.6 Tm max =1.657. In some embodiments of the present application, M 1 It can be one or more elements selected from Li, Ti, Zn, Mg, Sn, Al, Y, La, Nb, and Zr. ψLi = 2.413, ψTi = 1710, ψZn = 2.104, ψMg = 2.206, ψSn = 1.734, ψAl = 1.927, ψY = 2.100, ψLa = 2.113, ψNb = 1.750, ψZr = 1.830. M 1 With a value greater than ψ 0.6 Tm max The feeding property can make M 1 When the amount of sodium removal of the positive electrode material is x, 0.6≤x≤1, the electron donation to O is greater than that of the original transition metal element Tm, and the coordinated O has a higher electron density, which enhances the O-Na-O interaction. It can be understood that the element M 1The feeding property is as large as possible while satisfying the principle of equivalent substitution, which is more conducive to the enhancement of O-Na related effects.

[0062] In the implementation mode of the present application, M 2 To provide active elements for charge compensation, i.e. electrochemically active elements, doping elements M 2 Replace the Tm site in the transition metal layer and form part of the M 2 -O structure.M 2 As an active doping element, the feed rate ψ0.6M 2 Bigger M 2 It is more conducive to improving the high pressure stability of the material. The value of d represents M 2 In some embodiments of the present application, 0≤d≤0.2. In some embodiments of the present application, the value of d can be, for example, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2. In some embodiments of the present application, 0≤d≤0.1. The transition metal Tm layer is doped with the element M 2 The amount of Na is controlled within a suitable range. On the one hand, it is beneficial to increase the electron cloud density of O through its electron donation effect on O, so as to enhance the O-Na interaction and improve the structural stability of the positive electrode material under high voltage. On the other hand, appropriate doping is beneficial to the synthesis of pure phase, and for cost considerations, appropriate doping has a higher performance-efficiency ratio.

[0063] In some embodiments of the present application, c≥d, that is, in the positive electrode material, M 1 The doping ratio M 2 The doping amount is higher, which is beneficial to control costs while better improving the high-voltage stability of the positive electrode material.

[0064] In the implementation mode of the present application, ψ 0.6 M 2 >ψ 0.6 Tm max , M 2 It can be one or more elements selected from V, Cr, Ru, Cu, and Ir. 0.6 V=1.745,ψ 0.6 Cr=1.689,ψ 0.6 Ru=1.715,ψ 0.6 Cu=1.847,ψ 0.6 Ir=1.658. 0.6 M 2 >ψ 0.6 Tm max Can make M 2When the amount of sodium removal of the positive electrode material is x, 0.6≤x≤1, the electron donation to O is greater than that of the original transition metal element Tm, and the coordinated O has a higher electron density, which enhances the O-Na-O interaction. It can be understood that the element M 2 The feeding property is as large as possible while satisfying the principle of equivalent substitution, which is more conducive to the enhancement of O-Na related effects.

[0065] Considering the solid solubility problem, in some embodiments of the present application, M 2 When V is included, the content of V may be less than or equal to 0.1. Controlling the content of V within this range is beneficial to obtaining higher electrochemical performance. 2 When Cu is included, the content of Cu is less than or equal to 0.2. Controlling the content of Cu within this range is beneficial to obtaining higher electrochemical performance.

[0066] In the embodiment of the present application, the particle size D50 of the positive electrode material is 2μm-20μm. In some embodiments, the particle size of the positive electrode material can be 2μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm. The positive electrode material of the embodiment of the present application can be a spherical, polygonal or lamellar particle, or other morphology. In some embodiments, the positive electrode material is a flaky particle, the particle size (i.e., the sheet diameter) D50 is 2μm-20μm, and the particle thickness is 0.1μm-2μm. The particle thickness of the positive electrode material is 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm. Suitable particle size is conducive to the preparation of positive electrode sheets.

[0067] In the embodiment of the present application, the compaction density of the positive electrode material can be 2.8 g·cm -3 -3.2g cm -3 In some embodiments, the compaction density of the positive electrode material may be 2.8 g·cm -3 , 2.9 g·cm -3 , 3.0g·cm -3 、3.1g·cm -3 、3.2g·cm -3 The positive electrode material has a higher compaction density, which is beneficial to the improvement of battery capacity.

[0068] In the embodiment of the present application, the 0.2c charging capacity of the positive electrode material can be 140 mAh g -1 -180mAh g -1 In some embodiments, the 0.2c charge capacity of the positive electrode material is 145 mAh·g -1 -180mAh g-1 In some embodiments, the 0.2c charge capacity of the positive electrode material is 150 mAh·g -1 -160mAh g -1 The positive electrode material has a higher gram capacity, which is beneficial to the improvement of battery capacity.

[0069] In the embodiment of the present application, the crystal structure of the positive electrode material is an α-NaFeO2 hexagonal layered structure. The α-NaFeO2 hexagonal layered structure can make the positive electrode material have good electrochemical performance.

[0070] The positive electrode material of the embodiment of the present application can be characterized by XRD (X-ray diffraction), EDS (Energy Dispersive Spectrometer), EBSD (Electron Backscattered Diffraction) and other characterization methods to perform phase analysis, microstructure analysis and other characterization analyses.

[0071] The present application also provides a method for preparing the above-mentioned positive electrode material, comprising:

[0072] Step 1: According to the molecular formula of the positive electrode material Na 1-na A n+ a [M b M 1 c M 2 d ]O2, sodium source, A source, Tm source, M 1 Source, M 2 The sources are mixed to obtain a mixed material;

[0073] Step 2: calcining the mixture obtained in step 1 in an oxygen atmosphere to obtain a positive electrode material.

[0074] In step 1, the sodium source can be a sodium-containing compound, such as one or more of sodium carbonate, sodium nitrate, sodium oxide, sodium peroxide or sodium hydroxide. The A source can be an A-containing compound, such as one or more of carbonates, nitrates, oxides, peroxides, and hydroxides containing A. The Tm source can be a Tm-containing compound, such as one or more of metal oxides, metal carbonates, metal nitrates, and metal hydroxides containing Tm. When Tm in the molecular formula includes two or more metal elements, the Tm source can be a co-precipitated compound containing Tm, such as a metal co-precipitated carbonate, a metal co-precipitated hydroxide, etc. For example, the Tm source can be Ni 0.375 Fe 0.25 Mn 0.375 (OH)2.M1 The source can be M 1 Compounds, for example, may contain M 1 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides. 2 The source can be M 2 Compounds, for example, may contain M 2 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides.

[0075] In step 1, sodium source, A source, Tm source, M 1 Source, M 2 The sources are mixed, and a wall breaker can be used for mixing.

[0076] In step 2, the oxygen atmosphere can be an oxygen atmosphere or an air atmosphere. In some embodiments of the present application, the calcination can be a one-step calcination, and in other embodiments of the present application, the calcination can be a two-step or more-step calcination. After the calcined product is cooled to room temperature, it can be crushed and sieved to obtain a positive electrode material of a desired particle size.

[0077] Among them, when all raw materials are oxides, one-step calcination can be adopted, and the positive electrode material can be obtained by solid phase melt calcination after mixing. The one-step calcination can be 800℃-1100℃ for 10-20 hours. When each raw material includes non-oxides, two-step calcination can be performed, in which the non-oxide raw materials are decomposed into oxides by a first calcination, and then a second calcination is performed. The first calcination can be kept at 400℃-500℃ for 2-6 hours, and the second calcination can be kept at 800℃-1100℃ for 10-20 hours.

[0078] The method for preparing the positive electrode material in the embodiment of the present application has a simple process and does not require complicated steps during the doping process.

[0079] See also Figure 1 The present application also provides a positive electrode sheet 10, which includes the positive electrode material described in the present application. The positive electrode sheet prepared by using the positive electrode material described in the present application has a high capacity and high structural stability, and can effectively improve the cycle performance of the sodium ion battery while maintaining the high capacity of the sodium ion battery.

[0080] In the implementation mode of this application, Figure 1 As shown, the positive electrode sheet 10 includes a positive electrode current collector 11 and a positive electrode active layer 12 located on the positive electrode current collector 11. The positive electrode active layer 12 includes a positive electrode active material 121. The positive electrode active material 121 includes the positive electrode material Na 1-na A n+ a [M b M1 c M 2 d ]O2.

[0081] The positive electrode current collector 11 may be a metal foil, such as aluminum foil, gold foil, platinum foil, etc.

[0082] In some embodiments of the present application, the positive electrode active material 121 in the positive electrode active layer 12 is all positive electrode material Na 1- na A n+ a [M b M 1 c M 2 d In some embodiments, the positive electrode active material 121 in the positive electrode active layer 12 includes a positive electrode material Na 1- na A n+ a [M b M 1 c M 2 d ]O2, and also includes other positive electrode active materials. Other positive electrode active materials can be, for example, at least one of other layered sodium transition metal oxides, Prussian blue (white) compounds, and sodium polyanion compounds. In the embodiment of the present application, the layered sodium transition metal oxide can be, for example, sodium nickel iron manganese (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, abbreviated as NFM), the Prussian blue (white) type compound can be, for example, Prussian white (Na2Mn[Fe(CN)6], abbreviated as PBA), and the sodium polyanion type compound can be, for example, sodium iron phosphate (NaFePO4, abbreviated as NFP).

[0083] In some embodiments of the present application, the mass percentage of the positive electrode active material 121 in the positive electrode active layer 12 is greater than or equal to 92%.

[0084] In the embodiment of the present application, the positive electrode active layer 12 may further include a certain amount of binder, conductive agent and other components. The binder may be, for example, polyvinylidene fluoride (PVDF). The conductive agent may be, for example, amorphous carbon, carbon nanotubes, carbon fiber, graphene, etc. The above binder and conductive agent are only exemplary and are not limited thereto.

[0085] See also Figure 2The embodiment of the present application also provides a sodium ion battery 100, which includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the separator 30 is arranged between the positive electrode sheet 10 and the negative electrode sheet 20, and the electrolyte 40 is filled between the positive electrode sheet 10 and the negative electrode sheet 20 and infiltrates the separator 30. The negative electrode sheet 20 includes a negative electrode active material 221, and the negative electrode active material 221 includes a carbon material, wherein during charging, sodium ions are released from the positive electrode active material 121 of the positive electrode sheet 10, and are embedded in the negative electrode active material 221 of the negative electrode sheet 20 after passing through the electrolyte 40; during discharging, sodium ions are released from the negative electrode active material 221, and are inserted into the positive electrode active material 121 after passing through the electrolyte 40. The sodium ion battery of the embodiment of the present application adopts the positive electrode material Na 1-na A n+ a [Tm b M 1 c M 2 d ]O2 can effectively improve the cycle performance of sodium-ion batteries while maintaining their high capacity.

[0086] In the embodiment of the present application, the negative electrode sheet 20 includes a negative electrode current collector 21 and a negative electrode active layer 22 provided on the surface of the negative electrode current collector 21, wherein the negative electrode current collector 21 may be a metal foil, such as copper foil, aluminum foil, gold foil, platinum foil, etc. The negative electrode material layer includes a negative electrode active material 221, and the negative electrode active material 221 can accept and release sodium ions. In the embodiment of the present application, the negative electrode active material 221 includes a carbon material. In the embodiment of the present application, the carbon material may be one or more of natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, and porous carbon materials.

[0087] In the sodium ion battery 100, the electrolyte 40 is a transmission medium when sodium ions are transmitted between the positive electrode sheet 10 and the negative electrode sheet 20. In the embodiment of the present application, the electrolyte 40 includes an organic solvent, an electrolyte salt and an additive, wherein the electrolyte salt and the additive are both dissolved in the organic solvent.

[0088] In the embodiment of the present application, the organic solvent includes but is not limited to one or more of carbonate solvents, ether solvents, and carboxylate solvents. Among them, carbonate solvents include but are not limited to dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, trifluoromethyl ethylene carbonate, bis (2,2,2-trifluoroethyl) carbonate, (2,2,2-trifluoroethyl) methyl carbonate. One or more of ether solvents include but are not limited to tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and bis (2,2,2-trifluoroethyl) ether. Carboxylate solvents include but are not limited to one or more of methyl formate, ethyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl difluoroacetate, and methyl trifluoroacetate.

[0089] In the embodiment of the present application, the electrolyte salt includes but is not limited to NaClO4, NaBF4, NaPF6, NaAsF6, NaCF3SO3, NaTDI, Na[(CF3SO2)2N], Na[(FSO2)2N] and Na[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. In some embodiments of the present application, the molar concentration of the electrolyte salt in the electrolyte may be 0.01 mol / L-5.0 mol / L.

[0090] In the embodiment of the present application, the additives may include but are not limited to positive electrode film-forming additives, negative electrode film-forming additives, flame retardants, and the like.

[0091] In the embodiment of the present application, the diaphragm 30 includes but is not limited to single-layer polypropylene (PP), single-layer polyethylene (PE), double-layer PP / PE, double-layer PP / PP, three-layer PP / PE / PP and ceramic-coated PE.

[0092] See also Figure 3 The present application also provides an electric device 200, which includes the sodium ion battery 100 described above in the present application. The electric device using the sodium ion battery in the present application has high stability.

[0093] In the implementation manner of the present application, the electric device 200 may include an electronic device, an energy storage system, a communication device or a communication base station. Figure 3As shown, the power-consuming device 200 is an electronic device, which includes a housing 201, and electronic components and a battery 202 contained in the housing 201. The battery 202 supplies power to the electronic components, and the battery 202 includes the sodium ion battery 100 described above in the embodiment of the present application. In the present application, the power-consuming device 200 can be a consumer electronic product, such as a mobile phone, a tablet computer, a desktop computer, a laptop computer, a mobile power supply, a portable machine, a smart screen, a display, an audio system, a vehicle-mounted product, and other wearable or movable electronic devices (such as glasses, watches, bracelets, headphones, etc.), or a vehicle, an energy storage device, a communication device, a base station, and other equipment products.

[0094] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0095] Example 1

[0096] Na 0.94 Ca 0.03 Ni 0.5 Ti 0.5 Preparation of O2 layered cathode materials:

[0097] Na2CO3, CaO, NiO and TiO2 are added into a wall breaker according to the stoichiometric ratio for mixing. The mixed precursor is transferred into a sagger and then placed in an atmosphere furnace for calcination. Air is passed through the whole process. The calcination program sets the heating rate to 5℃ / min. After heating to 1000℃, the temperature is kept for 15 hours, cooled to room temperature, and the material is crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0098] Positive electrode preparation:

[0099] The obtained layered positive electrode material, conductive additive SP, and binder PVDF were mixed in weight proportions of 92 parts, 4 parts, and 4 parts, dissolved in solvent NMP, and stirred to obtain a uniform slurry. The slurry was then evenly coated on a carbon-coated aluminum foil, dried, and sliced ​​to obtain a positive electrode sheet.

[0100] Sodium ion battery preparation:

[0101] The prepared positive electrode sheet and the metallic sodium negative electrode are assembled into a sodium ion battery, and a carbonate electrolyte (1M NaClO4 dissolved in PC+5% FEC solution) is selected as the electrolyte.

[0102] Example 2

[0103] Na 0.94 Ca 0.03 Ni 0.4 Ti 0.5 Zn 0.1 Preparation of O2 layered cathode materials:

[0104] Na2CO3, CaO, NiO, TiO2 and ZnO were added into a wall breaker according to the stoichiometric ratio for mixing. The mixed precursor was transferred into a sagger and then placed into an atmosphere furnace for calcination. Air was passed through the whole process. The heating rate was set at 5°C / min. After heating to 1000°C, the temperature was kept for 15 hours and cooled to room temperature. The material was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0105] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0106] Example 3

[0107] Na 0.94 Ca 0.02 Li 0.02 Ni 0.5 Ti 0.5 Preparation of O2 layered cathode materials:

[0108] Na2CO3, CaO, Li2CO3, NiO and TiO2 are added into a wall breaker according to the stoichiometric ratio for mixing. The mixed precursor is transferred into a sagger and then placed in an atmosphere furnace for calcination. Air is passed through the whole process. The calcination program sets the heating rate to 5℃ / min. After heating to 1000℃, the temperature is kept for 15 hours, cooled to room temperature, and the material is crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0109] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0110] Example 4

[0111] Na 0.94 Ca 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0112] Take Na2CO3, CaO, Ni according to the stoichiometric ratio 0.33 Fe 0.33 Mn 0.33 (OH)2, CuO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0113] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0114] Example 5

[0115] Na 0.94 Mg 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.067 Ti 0.133 Preparation of O2 layered cathode materials:

[0116] Take Na2CO3, MgO, Ni according to the stoichiometric ratio 0.33 Fe 0.33 Mn 0.33 (OH)2, Li2CO3, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process, and the temperature is kept at 450°C for 6 hours, and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process, and the temperature is kept at 1000°C for 15 hours, followed by natural cooling. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0117] Figure 4 The positive electrode material Na provided in Example 5 of the present application 0.94 Mg 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.067 Ti 0.133 EDS element distribution diagram of O2, Figure 4 The element distribution diagram shows that the obtained positive electrode material contains Na, Mg, Ni, Fe, Mn, Ti, and O.

[0118] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0119] Example 6

[0120] Na 0.94 Li 0.06 Ni 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0121] According to the stoichiometric ratio, Na2CO3, Li2CO3, Ni 0.33 Fe 0.33 Mn0.33 (OH)2, CuO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0122] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0123] Example 7

[0124] Na 0.94 Mg 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0125] Take Na2CO3, MgO, Ni according to the stoichiometric ratio 0.33 Fe 0.33 Mn 0.33 (OH)2, CuO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0126] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0127] Example 8

[0128] Na 0.94 Mg 0.03 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0129] Take Na2CO3, MgO, Ni according to the stoichiometric ratio 0.33 Fe 0.33 Mn 0.33(OH)2, ZnO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in a wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0130] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0131] Example 9

[0132] Na 0.94 Mg 0.03 Ni 0.3 Fe 0.2 Mn 0.3 Al 0.05 Ti 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0133] Take Na2CO3, MgO, Ni according to the stoichiometric ratio 0.375 Fe 0.25 Mn 0.375 (OH)2, TiO2, Li2CO3, and Al2O3 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process, and the temperature is kept at 450°C for 6 hours, and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process, and the temperature is kept at 1000°C for 15 hours, followed by natural cooling. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0134] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0135] Example 10

[0136] Na 0.94 Ca 0.03 Ni 0.3 Fe 0.2 Mn 0.3 Co 0.05 Ti 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0137] Take Na2CO3, CaO, Ni in stoichiometric ratio 0.375 Fe 0.25 Mn0.375 (OH)2, Co2O3, TiO2, and Li2CO3 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0138] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0139] Embodiment 11

[0140] Na 0.94 Li 0.06 Ni 0.3 Fe 0.2 Mn 0.3 V 0.05 Ti 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0141] Take Na2CO3, Li2CO3, Ni 0.375 Fe 0.25 Mn 0.375 (OH)2, TiO2, Li2CO3, and V2O5 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0142] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0143] Example 12

[0144] Na 0.94 Ca 0.03 Ni 0.3 Fe 0.2 Mn 0.3 Cr 0.05 Ti 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0145] Take Na2CO3, CaO, Ni in stoichiometric ratio 0.375 Fe0.25 Mn 0.375 (OH)2, TiO2, Li2CO3, and Cr2O3 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0146] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0147] Example 13

[0148] Na 0.94 Ca 0.03 Ni 0.3 Fe 0.2 Mn 0.3 Ru 0.05 Sn 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0149] Take Na2CO3, CaO, Ni in stoichiometric ratio 0.375 Fe 0.25 Mn 0.375 (OH)2, SnO2, Li2CO3, and RuO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0150] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0151] Embodiment 14

[0152] Na 0.93 Li 0.07 Ni 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0153] According to the stoichiometric ratio, Na2CO3, Li2CO3, Ni 0.33 Fe0.33 Mn 0.33 (OH)2, CuO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0154] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0155] Embodiment 15

[0156] Na 0.94 Ca 0.03 Ni 0.4 Mn 0.4 Zn 0.1 Ti 0.1 Preparation of O2 layered cathode materials:

[0157] Na2CO3, CaO, NiO, MnO2, TiO2 and ZnO were added into a wall breaker according to the stoichiometric ratio for mixing. The mixed precursor was transferred into a sagger and then placed in an atmosphere furnace for calcination. Air was passed through the whole process. The heating rate was set at 5°C / min. After heating to 1000°C, the temperature was kept for 15 hours and cooled to room temperature. The material was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0158] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0159] Example 16

[0160] Na 0.94 Li 0.06 Ni 0.3 Fe 0.2 Mn 0.3 V 0.1 Ti 0.067 Li 0.033 Preparation of O2 layered cathode materials:

[0161] Take Na2CO3, Li2CO3, Ni 0.375 Fe 0.25 Mn 0.375(OH)2, TiO2, Li2CO3, and V2O5 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0162] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0163] Embodiment 17

[0164] Na 0.94 Li 0.06 Ni 0.3 Fe 0.2 Mn 0.3 V 0.11 Ti 0.06 Li 0.03 Preparation of O2 layered cathode materials:

[0165] Take Na2CO3, Li2CO3, Ni 0.375 Fe 0.25 Mn 0.375 (OH)2, TiO2, Li2CO3, and V2O5 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the temperature is kept for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the temperature is kept for 15 hours. The temperature is then naturally lowered. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0166] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0167] Embodiment 18

[0168] Na 0.94 Mg 0.03 Ni 0.3 Fe 0.2 Mn 0.27 Al 0.08 Ti 0.1 Li 0.05 Preparation of O2 layered cathode materials:

[0169] Take Na2CO3, MgO, Ni according to the stoichiometric ratio 0.375 Fe 0.25Mn 0.375 (OH)2, TiO2, Li2CO3, and Al2O3 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process, and the temperature is kept at 450°C for 6 hours, and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process, and the temperature is kept at 1000°C for 15 hours, followed by natural cooling. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0170] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0171] Embodiment 19

[0172] Na 0.95 Li 0.05 Ni 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0173] According to the stoichiometric ratio, Na2CO3, Li2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2, CuO, and TiO2 are added to a wall breaker for mixing. The mixed precursors are transferred to a sagger and then placed in an atmosphere furnace for calcination. The calcination is divided into two stages with air. The heating rate is set at 3°C / min for the first calcination process. After the temperature reaches 450°C, the mixture is kept warm for 6 hours and then cooled to room temperature. The second mixing is carried out in the wall breaker and the second calcination is carried out again. The heating rate is set at 5°C / min for the second calcination process. After the temperature reaches 1000°C, the mixture is kept warm for 15 hours and then cooled naturally. After the material is discharged, it is crushed by a pulverizer and passed through a 200-mesh sieve to obtain the positive electrode material.

[0174] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0175] Comparative Example 1

[0176] Preparation of NaNiO2 layered cathode materials:

[0177] Take Na2O2 and NiO according to the stoichiometric ratio, add them into the wall breaking machine for mixing, take them out after the mixture is mixed, transfer them into a sagger, and calcine them in an atmosphere furnace in an oxygen atmosphere. The calcination program sets the heating rate to 5℃ / min, and after heating to 800℃, keep warm for 12 hours. Transfer the above mixed precursor into a sagger, and then place it in an atmosphere furnace for calcination. The whole process is calcined with air. The calcination program sets the heating rate to 5℃ / min, and after heating to 1000℃, keep warm for 15 hours. Cool it to room temperature, and crush it into a grinder after discharging it. Pass it through a 200-mesh sieve to obtain a layered positive electrode material.

[0178] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0179] Comparative Example 2

[0180] Na 0.94 Ca 0.03 Preparation of NiO2 layered cathode material:

[0181] According to the stoichiometric ratio, Na2O2, CaO and NiO are added to the wall breaking machine for mixing, and then taken out after the mixing is completed. The mixed precursor is transferred to a sagger, and then placed in an atmosphere furnace for calcination. The whole process is calcined with oxygen. The calcination program is set to a heating rate of 5℃ / min. After heating to 750℃, it is kept warm for 15 hours, cooled to room temperature, and crushed by a pulverizer after discharging, and passed through a 200-mesh screen to obtain the positive electrode material.

[0182] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0183] Comparative Example 3

[0184] NeNi 0.5 Ti 0.5 Preparation of O2 layered cathode materials:

[0185] Accurately weigh Na2CO3, NiO and TiO2 according to the stoichiometric ratio and add them into the wall breaking machine for mixing, and take them out after mixing.

[0186] The mixed precursor was transferred to a sagger and then placed in an atmosphere furnace for calcination. Air was passed through the whole process. The calcination program was set to a heating rate of 5°C / min. After heating to 1000°C, it was kept warm for 15 hours. The mixed precursor was transferred to a sagger and then placed in an atmosphere furnace for calcination. Air was passed through the whole process. The calcination program was set to a heating rate of 5°C / min. After heating to 1000°C, it was kept warm for 15 hours. It was cooled to room temperature. After discharging, it was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0187] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0188] Comparative Example 4

[0189] NeNi0.4 Ti 0.5 Zn 0.1 Preparation of O2 layered cathode materials:

[0190] Na2CO3, NiO, TiO2, and ZnO were accurately weighed according to the stoichiometric ratio and added into a wall breaking machine for mixing. The mixed precursor was transferred into a sagger and then placed in an atmosphere furnace for calcination. Air was passed through the whole process of calcination. The calcination program set the heating rate to 5°C / min. After heating to 1000°C, the temperature was kept for 15 hours, cooled to room temperature, and the material was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0191] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0192] Comparative Example 5

[0193] NeNi 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05 Preparation of O2 layered cathode materials:

[0194] Na2CO3, NiO, Fe2O3, MnO2, CuO, and TiO2 were accurately weighed according to the stoichiometric ratio and added into a wall breaking machine for mixing. The mixed precursors were transferred to a sagger and then placed in an atmosphere furnace for calcination. Air was passed through the entire calcination process. The heating rate was set at 5°C / min. After heating to 1000°C, the temperature was kept for 15 hours, cooled to room temperature, and the material was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0195] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0196] Comparative Example 6

[0197] Na 0.94 Ca 0.03 Ni 0.5 Mn 0.5 Preparation of O2 layered cathode materials:

[0198] Na2CO3, CaO, NiO, TiO2 and ZnO were added into a wall breaker according to the stoichiometric ratio for mixing. The mixed precursor was transferred into a sagger and then placed into an atmosphere furnace for calcination. Air was passed through the whole process. The heating rate was set at 5°C / min. After heating to 1000°C, the temperature was kept for 15 hours and cooled to room temperature. The material was crushed by a pulverizer and passed through a 200-mesh sieve to obtain a layered positive electrode material.

[0199] The preparation of the positive electrode sheet and the sodium ion battery is the same as in Example 1.

[0200] Comparative Example 7

[0201] The commercial cathode material NaNi 0.33 Fe 0.34 Mn 0.33 O2 uses the method of Example 1 to prepare the positive electrode sheet and the sodium ion battery.

[0202] The maximum sodium removal amount before phase change, phase change capacity, and 300-cycle capacity retention rate of the sodium ion batteries of Examples 1 to 19 and Comparative Examples 1 to 7 were measured. The measurement results are shown in Table 1.

[0203] The maximum amount of sodium removal before phase change reflects the maximum reversible capacity of the material before the irreversible phase change, which is equal to the ratio of the capacity before the charging phase change platform to the theoretical capacity. For example, for NaNiO2, assuming that the capacity before the high-voltage phase change platform is 140mAh / g, and the theoretical capacity of NaNiO2 is 235.7mAh / g, it can be calculated that the maximum amount of sodium removal before phase change = 140 / 235.7 = 0.59. Test method: At 0.2C, the first charge is carried out at a current density of 32mA / g to obtain the first charging curve of the material. Two slopes are made for the curves before and after the phase change, and the sodium removal corresponding to the intersection is the maximum sodium removal before the phase change.

[0204] The phase change capacity reflects the degree of participation in the irreversible phase change. The larger the phase change capacity, the larger the irreversible capacity. Test method: At 0.2C, the first charge is performed at a current density of 32mA / g to obtain the first charge capacity of the material. The difference between the first charge capacity and the capacity corresponding to the maximum sodium removal amount of the material is the phase change capacity.

[0205] The 300-cycle capacity retention rate is the ratio of the battery's 300th cycle capacity to the first cycle capacity. Test method: Perform 300 cycles of charge and discharge at 1C with a current density of 160mAh / g, and calculate the capacity retention rate.

[0206] Figure 5 The maximum sodium removal amount curve of the positive electrode material before phase change provided in Example 9 of the present application; Figure 5 It can be seen that the maximum sodium removal amount of the positive electrode material of Example 9 before the phase change is 0.63.

[0207] Figure 6 The phase change capacity curve diagram of the positive electrode material provided in Example 9 of the present application; Figure 6 It can be seen that the phase change capacity of the positive electrode material of Example 9 is 18.

[0208] Figure 7 The maximum sodium removal amount curve of the positive electrode material before phase change provided in Comparative Example 7 of the present application; Figure 7 It can be seen that the maximum sodium removal amount of the positive electrode material of Comparative Example 7 before phase change is 0.58.

[0209] Figure 8 Phase change capacity curve diagram of the positive electrode material provided in Comparative Example 7 of the present application; Figure 8 It can be seen that the phase change capacity of the positive electrode material of Comparative Example 7 is 34.

[0210] Table 1

[0211]

[0212]

[0213] It can be seen from Table 1 that compared with the positive electrode material NaNiO2 of comparative example 1, the positive electrode materials of Examples 1 to 17 of the present application, through co-doping with the sodium layer and the transition metal layer, have an increased maximum sodium removal amount before phase change, and a significantly decreased phase change capacity, that is, the high-voltage phase change stability is improved, and at the same time, the 300-cycle capacity retention rate is significantly improved.

[0214] Compared with the positive electrode material NaNiO2 of Comparative Example 1, the positive electrode material Na 0.94 Ca 0.03 NiO2, and the positive electrode material NaNi of Comparative Example 3 0.5 Ti 0.5 O2, the positive electrode materials of Examples 1 to 3 of the present application are co-doped with the sodium layer and the transition metal layer, and the maximum amount of sodium removal before the phase change is improved, and the phase change capacity is significantly reduced, that is, the high voltage phase change stability is improved, and the 300 cycle capacity retention rate is significantly improved. This is mainly due to the multi-element co-doping of the sodium layer and the transition metal layer, which gives full play to the synergistic effect between the elements, thereby significantly improving the electrochemical properties of the positive electrode material.

[0215] Compared with the positive electrode material NaNi of Comparative Example 4 0.4 Ti 0.5 Zn 0.1 O2, the positive electrode material Na of Example 2 of the present application 0.94 Ca 0.03 Ni 0.4 Ti 0.5 Zn 0.1 O2, through sodium layer doping, its maximum sodium removal amount before phase change is improved, the phase change capacity is significantly reduced, and the 300-cycle capacity retention rate is significantly improved.

[0216] Compared with the positive electrode material NaNi of Comparative Example 5 0.3 Fe 0.3 Mn 0.3 Cu 0.05 Ti 0.05O2, the positive electrode materials of Examples 4, 6, 7, 14 and 19 of the present application are co-doped with a sodium layer and a transition metal layer, and their maximum sodium removal amount before phase change is significantly improved, the phase change capacity is significantly reduced, and the 300-cycle capacity retention rate is significantly improved.

[0217] Compared with the positive electrode material Na 0.94 Ca 0.03 Ni 0.5 Mn 0.5 O2. The positive electrode material of Example 15 of the present application is co-doped with a sodium layer and a transition metal layer, and its maximum sodium removal amount before phase change is significantly improved, the phase change capacity is significantly reduced, and the 300-cycle capacity retention rate is significantly improved.

[0218] Compared with the positive electrode material NaNi of Comparative Example 7 0.33 Fe 0.34 Mn 0.33 O2, the positive electrode materials of Examples 4-14 and Examples 16-19 of the present application are co-doped with a sodium layer and a transition metal layer, and their maximum sodium removal amount before phase change is significantly improved, the phase change capacity is significantly reduced, and the 300-cycle capacity retention rate is significantly improved.

[0219] Depend on Figures 5 to 8 It can be seen that compared with the positive electrode material NaNi of Comparative Example 7 0.33 Fe 0.34 Mn 0.33 O2, the positive electrode material Na of Example 9 of the present application 0.94 Mg 0.03 Ni 0.3 Fe 0.2 Mn 0.3 Al 0.05 Ti 0.1 Li 0.05 O2, by doping the sodium layer with an appropriate amount of magnesium and the transition metal layer with an appropriate amount of Al, Ti, and Li, the maximum sodium removal amount of the positive electrode material before the phase change is significantly increased, and the phase change capacity is significantly decreased.

[0220] Comparing Examples 1 to 3, it can be seen that the positive electrode material Na 0.94 Ca 0.03 Ni 0.4 Ti 0.5 Zn 0.1 O2 is doped with multiple elements through the transition metal layer, and its performance is improved compared with the positive electrode material of Example 1; the positive electrode material Na of Example 3 0.94 Ca 0.02 Li 0.02 Ni 0.5 Ti 0.5 O2 is doped with multiple elements through the sodium layer, and the performance is improved compared with the positive electrode material of Example 1.

[0221] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.

[0222] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0223] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0224] Likewise, "at least one" means one or more, and "a plurality of" means two or more.

[0225] In this application, “-” represents a range value, including the endpoint values ​​at both ends. For example, the value of a can be 0.5-15, which means that the value of a can be between 0.5 and 15, and includes the endpoint values ​​0.5 and 15.

[0226] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

Claims

1. A positive electrode material, characterized in that: The molecular formula of the positive electrode material is Na 1-na A n+ a [Tm b M 1 c M 2 d ]O2, wherein A is one or more alkali metal or alkaline earth metal elements with a power feeding property ψA satisfying 0.9ψNa≤ψA<ψNa; Tm is a combination of one or more elements of Fe, Mn, Co and Ni, M 1 is the feeding characteristic ψM 1 Satisfy ψM 1 >ψ 0.6 Tm max One or more metal elements, and M 1 M is an inert element that does not provide charge compensation. 2 The feeding characteristic ψ 0.6 M 2 Satisfy ψ 0.6 M 2 >ψ 0.6 Tm max One or more metal elements, and M 2 An active element that provides charge compensation; 0<a≤0.1, 0.3≤b<1, 0<c≤0.6, 0≤d≤0.2, b+c+d=1, and the values ​​of a, b, c, d enable the positive electrode material to maintain charge balance; Among them, ψA=χO-χA; ψM 1 =χO-χM 1 , χO is the effective electronegativity of O, χA is the effective electronegativity of A, χM 1 M 1 The effective electronegativity of 0.6 Tm max is the maximum chargeability of Tm when the amount of sodium removal of the positive electrode material is greater than or equal to 0.6, where ψ 0.6 Tm = ψiniTm-0.6*(ψiniTm-ψendTm), ψiniTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 0, and ψendTm is the power feeding property of Tm when the amount of sodium removal of the positive electrode material is 1; ψ 0.6 M 2 =ψiniM 2 -0.6*(ψiniM 2 -ψendM 2 ), ψiniM 2 When the amount of sodium removed from the positive electrode material is 0, M 2 The feeding property, ψendM 2 When the amount of sodium removed from the positive electrode material is 1, M 2 The feeding property.

2. The positive electrode material according to claim 1, characterized in that 0.01≤a≤0.06。 3. The positive electrode material according to claim 1 or 2, characterized in that 0.4≤b≤0.9。 4. The positive electrode material according to any one of claims 1 to 3, characterized in that 0.05≤c≤0.2。 5. The positive electrode material according to any one of claims 1 to 4, characterized in that 0≤d≤0.1。 6. The positive electrode material according to any one of claims 1 to 5, characterized in that The A is selected from one or more elements of Li, Mg, Ca, Sr, and Ba.

7. The positive electrode material according to any one of claims 1 to 6, characterized in that The M 1 One or more elements selected from Li, Ti, Zn, Mg, Sn, Al, Y, La, Nd, and Zr.

8. The positive electrode material according to any one of claims 1 to 7, characterized in that The M 2 One or more elements selected from V, Cr, Ru, Cu, and Ir.

9. The positive electrode material according to any one of claims 1 to 8, characterized in that The positive electrode material is in the form of spherical, polygonal or lamellar particles, and the particle size D50 is 2 μm-20 μm.

10. The positive electrode material according to any one of claims 1 to 9, characterized in that The compaction density of the positive electrode material is 2.8 g·cm -3 -3.2g cm -3 .

11. The positive electrode material according to any one of claims 1 to 10, characterized in that The gram capacity of the positive electrode material is 140 mAh g -1 -180mAh g -1 .

12. The positive electrode material according to any one of claims 1 to 11, characterized in that The crystal structure of the positive electrode material is an α-NaFeO2 hexagonal layered structure.

13. A method for preparing the positive electrode material according to any one of claims 1 to 12, characterized in that: include: According to the molecular formula of the positive electrode material Na 1-na A n+ a [Tm b M 1 c M 2 d ]O2, sodium source, A source, Tm source, M 1 Source, M 2 The sources are mixed to obtain a mixed material; The mixed material is calcined in an oxygen atmosphere to obtain a positive electrode material.

14. The preparation method according to claim 13, characterized in that: The sodium source includes a sodium-containing compound, and the sodium-containing compound includes one or more of sodium carbonate, sodium nitrate, sodium oxide, sodium peroxide and sodium hydroxide; the A source includes an A-containing compound, and the A-containing compound includes one or more of carbonates, nitrates, oxides, peroxides and hydroxides containing A; the Tm source includes a Tm-containing compound, and the Tm-containing compound includes one or more of metal oxides, metal carbonates, metal nitrates and metal hydroxides containing Tm; the M 1 Sources include M 1 Compound, the compound containing M 1 Compounds including M 1 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides; the M 2 Sources include M 2 Compound, the compound containing M 2 Compounds including M 2 One or more of carbonates, nitrates, oxides, peroxides, and hydroxides.

15. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 12.

16. The positive electrode sheet according to claim 15, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on the positive electrode current collector, and the positive electrode active layer includes the positive electrode material.

17. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte and a separator located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the positive electrode sheet according to claim 15 or 16.

18. An electrical equipment, characterized in that: The electrical equipment comprises the sodium ion battery according to claim 17.

19. The electrical equipment according to claim 18, characterized in that the electrical equipment comprises an electronic device, an energy storage system, a communication device or a communication base station.